The Ngampang Punishment as a Customary Punishment for Indigenous People of Dayak Kebahan in West Borneo: A Juridical Normative Review - Henny Damaryanti; Yenny AS; Hendrik Hendrik (Proceedings of AICS - Social Sciences, 2018)
Ngampanghas a similarity to adultery that regulated in Article 284 of the Criminal Code. In the life of Dayak indigenous peoples in Kebahan, West Borneo, ngampangis a deeds committed by man and woman that resulted in pregnancy and the birth of children out of wedlock. Ngampangis believed to be destructive of the life order of Dayak customary community of Kebahan and is believed to wreak havoc for the village in the territory of indigenous peoples, hence the custom sanctions are applied to restore the balance between the real and the spirit world. In the past, sanctions against actors in the form of adatreactions, ostracized from indigenous peoples, scorned, to the heaviest expulsion from villages accompanied by the payment of fines in the form of tawak singkap(gong) and pa singkapor sipe(a kind of copper tray). Ngampanghave different values of punishment and decision of custom to bachelor, virgin, male or female married women, couple ngampang"so" (express ready to marriage stage), ngampang"not so" (male- men are not willing to be responsible), and ngampang(pregnant women but did not find a partner). It can also be punished criminally only if there is one party who feels aggrieved as a rape victim. Ngampangmust be completed and decided by the village team assisted by the head of the hamlet as a member. This study is a normative juridical study, using secondary data in the form of legislation related to ngampang(adultery), type of adatngampangsanctions, custom sanction settlement procedures, documents and writings. Data analysis method used is descriptive qualitative, poured in the form of logical and systematic description.Keywords:customary sanction, ngampang, Dayak Kebahan.